Variation in Some Blood Parameters of Geese Subjected to Feather Gathering - Toth, Peter; Janan , Janbaz (International Journal of Poultry Science, 2016)
Two experiments were conducted on 50 (25♂, 25♀) geese of Babat Hungarian Upgraded breed during their post-breeding moulting period to measure stress response to feather gathering. They were assigned to five treatment groups in both experiments: (1) control, (2) gathered, (3) given anti-stress supplement before gathered, (4) sham gathered and (5) given anti-stress supplement before sham gathered. In Experiment 1 blood samples were taken one hour before and one hour after the procedures and plasma levels of thyroxin (T4) and triiodothyronine (T3) were measured by radioimmunoassay. The concentrations of both T4 and T3 decreased post-exposure indicating a mild to moderate distress. In Experiment 2 blood samples were taken 24 h and 7 days post-procedures for determining total white blood cell counts and the heterophil granulocyte to lymphocyte (H/L) ratios. Feather gathering caused a mild stress that affected circulating white blood cells. However, the H/L method on its own is not a reliable stress indicator of the feather gathering procedure. The anti-stress supplement seemed to have little effect on the thyroid hormones levels or the haematological variables.